Substantial Illicit, Fundamental Element to Configure the Disciplinary Lack (2017)
This article aims to analyze the material unlawfulness as key to shaping the disciplinary offense. At this point in both the rise of disciplinary control entity such as the Attorney General's Office, should be analyzed when truly a public servant or an individual in the exercise of public functions is transgressing the functional duty, which is a sine qua non under disciplinary code in order to constitute only a misdemeanor. It also seeks to show that sometimes there is typically, this is not subject to sanctions because the offending agent with his conduct did not affect their functions, as defined by the constitutional court to the disciplinary law is interested in conduct that affects the normal development of the public service. And finally defined as the unlawful Illegality substantial differ.